Mission planning problem for optical video satellite imaging with variable image duration: A greedy algorithm based on heuristic knowledge. Issue 11 (1st December 2020) - Chang, Zhongxiang; Chen, Yuning; Yang, Wenyuan; Zhou, Zhongbao
Abstract: The video optical satellite with the capability of active imaging is a new generation of earth observation satellite (EOS). The image duration of each observation task can be variable. By the way, EOS can image ground targets continuously during a time period, which is very suitable in the application of monitoring for important ground targets. However, the novel capability brings new challenges to satellite imaging mission planning and makes the problem more complicated. In this paper, we study a mission planning problem for optical video satellite with variable image duration (MPPVID) and propose a dedicated method to calculate the image duration of each observation task considering their priority and workpiece congestion. Based on a simple heuristic greedy algorithm (SHGA), two types of tests, a single test and an integral test, are investigated. In both tests, we thoroughly analyze the effects of variable image duration on solving MPPVID. By the way, we summarize a series of useful heuristic knowledges to guide setting the image duration for each observation task fast, and we also analyze the improvement for SHGA brought by these heuristic knowledges.